Revolutionary love : a political manifesto to heal and transform the world - Lerner, Michael, 1943- (S. Mark Taper Foundation imprint in Jewish studies., 2019)
"For those who are tired of screaming across the table as they debate the future of the country and the planet, Revolutionary Love brings hope, respect, and love to today's political divide. Michael Lerner offers concrete solutions for future development by identifying why the Left and the Right have been so ineffective in achieving any lasting change and discussing what it will take to actually heal and repair the world, both spiritually and physically. He reminds us that ethical and spiritual qualities--compassion, respect, love, and a strong sense of community--can bring people together in a beneficial and constructive way that has the possibility of effecting real change. A daring book on an urgent topic, Revolutionary Love aims to reunite all sections of the population into a positive democratic force capable of reversing the downward trajectory of our world. It is about a fundamental transformation of collective thinking and acting that unites us for the greater good of all people"--Provided by publisher.